PERFORMANCE ASSESSMENT AND EVALUATION OFCURVING MACHINE OPERATOR AT PT.XYZ USING ANALYTICAL HIERARCHY PROCESS(AHP) AND RATING SCALE - muhammad rusdi (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2018)
PT. XYZ is a company engaged in manufacturing the defense and security products for military and commercial, which consists of 20% of military products and 80% of commercial products. This study aims to determine the performance assessment of the curving machineoperators in PT.XYZ. Previously, the system of operator's performance assessment has an incomplete criterion that is less likely to reflect actual operator performance and the absence of reference data for annual bonus sharing. To get an accurate operator performance, then conducted an assessment based on the Spencer competency owned by each operator. The dimensions of this assessment are based on objective and subjective judgments. Research data were collected by observation and filling out the questionnaire.Then, data were analyzed using Expert Choice software. The method of Analytic Hierarchy Process (AHP) was chosen in accordance with the research problems and objectives. After obtaining the final result of weight of Analytic Hierarchy Process (AHP), the next performance assessment was done by integration with Rating Scale method. The results show that there is a difference in the measurement of performance evaluation of the prior and new method, this is due to additionalcriteria taken into the new assessment, including absenteeism (presence), quantity of work, work quality, work safety, teamwork, and so forth.